2020
DOI: 10.3390/educsci10070187
|View full text |Cite
|
Sign up to set email alerts
|

Generation Z: Fitting Project Management Soft Skills Competencies—A Mixed-Method Approach

Abstract: Generation Z is arriving in the workforce. Do these youngsters have the skills and traits to fit project teams? This study reviews the literature concerning project management competencies and the traits that are associated with Generation Z. To deepen the understanding of its members (Gen Zers) traits, we explore the self-awareness of their profile, strengths and weaknesses with an empirical study. We used a mixed-method approach, implementing a survey on a sample of 211 college students about to enter the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 77 publications
(99 reference statements)
2
56
0
10
Order By: Relevance
“…The fundamental objective of this research work is to investigate the influence of personality traits (the big five model) exhibited by project managers on project success, with moderating role of external environmental factors. Literature is available on finding the effects of personality in terms of job performance [8], organizational commitment [9], and job satisfaction. However, the literature on project success factors has overlooked the impact of project managers' personalities on project success regarding implications of external environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental objective of this research work is to investigate the influence of personality traits (the big five model) exhibited by project managers on project success, with moderating role of external environmental factors. Literature is available on finding the effects of personality in terms of job performance [8], organizational commitment [9], and job satisfaction. However, the literature on project success factors has overlooked the impact of project managers' personalities on project success regarding implications of external environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, literature shows that soft competencies play an essential role in research project management [69][70][71][72][73][74][75][76], and PRs in the academic context need managerial skills [35,43,53]. In academic research management, leadership skills and self-efficacy are shown to be crucial: Leadership weaknesses are listed among the main problems in research project implementation and prevent projects from achieving success [43,53,77].…”
Section: The Role Of Soft Skills In Randd Project Managementmentioning
confidence: 99%
“…Bearing in mind that, "[t]o establish relationships, they prefer social media to face-to-face communication" (Vizcaya-Moreno & Pérez-Cañaveras, 2020, p. 1), their attention span is short (Giunta, 2017;Magano et al, 2020), they favour visual media and, thus, "visual forms of learning" (Poláková & Klímová, 2019, p. 14), flexibility and "hands-on opportunities that prepare them for career success" (Seemiller & Grace, 2017, p. 24), then, in education, this calls for the use of multiple content domains in a single lesson and invites a multidisciplinary approach with tasks that promote metacognition, interaction, learning and transfer. A very good approach that has proven successful is the introduction of virtual collaborative learning through telecollaboration, which can be defined as … the process of communicating and working together with other people or groups from different locations through online or digital communication tools (e.g., computers, tablets, cellphones) to co-produce a desired work output.…”
Section: Integrating Technologies and Project-based Learning Into Foreign Language Teachingmentioning
confidence: 99%